(untitled) (Research, Society and Development, 2019)
Despite of emergence on the 70’s on the education field and being consolidate around a decade later, the biographical research is still poorly understood by some researchers and not fully accepted by some members of the scientific academy. The explanation most discussed by theorists is related to the positivist perspective that persists even on human sciences. Considering this, the purpose of this article is to elucidate what are the bases of a biographical research from an introductory perspective and why is it important in teacher’s and professor’s formations, presenting suggestion to further studies and interventions on this area. In order to carry out this study, prominent authors on the fields of biographical research and teacher’s formations were highlight and brought to a discussion summarizing their main ideas. This study is justified by the belief that this research may help educators and researchers with their practices in any area of the education field by introducing them this methodology. As results, the article highlights the importance of biographical research on the process of pursing the self-awareness when teaching.